Baseline Information of Floral and Faunal Diversity for Long Term Ecological Monitoring of Dhanolti Eco Park - Mussoorie forest Division, Uttarakhand - Virkar, Preeti S.; Uniyal, V. P.; Banerjee, A. K. (Indian Forester, 2012)
Long term ecological monitoring of biodiversity is practicable with an inventory of its floral and faunal diversity. With this view, the documentation of biodiversity of the two fenced areas of Dhanolti reserve forest of Mussoorie forest division has been prepared (Site 1 and Site 2). Long term ecological monltoring locations were established for assigning changes in the biodiversity of the fenced area.